2000
DOI: 10.1038/sj.bjp.0703478
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal noradrenergic neurotransmission in concurrent EEG desynchronization and inhibition of penile erection induced by cocaine in the rat

Abstract: 1 We previously reported that cocaine may induce activation of cortical (cEEG) and hippocampal (hEEG) electroencephalographic signals, concurrent with inhibition of penile erection, via an action on the hippocampal formation. The present study further evaluates the role of noradrenergic neurotransmission at the hippocampal formation in this process, using adult, male Sprague-Dawley rats anaesthetized and maintained by chloral hydrate. 2 Unilateral microinjection of cocaine (100 nmoles) into the hippocampal CA1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…Thus, it is conceivable that ascending sensory afferents initiated by tumescence of the penis may activate those hippocampal neurons that subserve the negative feedback mechanism via chemical mediators other than glutamate or oxytocin. That this chemical mediator may be norepinephrine was suggested in a recent study (Chang et al, 2000). We observed that cocaine may inhibit penile erection by triggering the descending limb of the feedback inhibitory mechanism via noradrenergic neurotransmission in the HF.…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…Thus, it is conceivable that ascending sensory afferents initiated by tumescence of the penis may activate those hippocampal neurons that subserve the negative feedback mechanism via chemical mediators other than glutamate or oxytocin. That this chemical mediator may be norepinephrine was suggested in a recent study (Chang et al, 2000). We observed that cocaine may inhibit penile erection by triggering the descending limb of the feedback inhibitory mechanism via noradrenergic neurotransmission in the HF.…”
Section: Introductionmentioning
confidence: 59%
“…These included norepinephrine (Sigma, St. Louis, MO), phenylephrine (Sigma), BHT 933 (RBI, Natick, MA), prazosin (Sigma), naftopidil (RBI), yohimbine (Sigma), rauwolscine (RBI), and papaverine (U-Liang Pharmaceuticals, Taiwan, Republic of China). The doses used were exactly the same as in our previous study (Chang et al, 2000), in which these test agents were used for the same purpose as in the present study. With the exception of naftopidil and papaverine, which used, respectively, 20% methanol and saline as the solvent, all test agents were dissolved in artificial cerebrospinal fluid (aCSF).…”
Section: Test Agentsmentioning
confidence: 98%
“…This included cannulation of the left femoral artery and vein for the measurement of systemic arterial pressure (SAP) and maintenance of anaesthetic level by intravenous infusion of chloral hydrate (40 mg kg h −1 ). Previous studies (Chang et al ., 1998a, 1998b; 2000; 2001) indicated that this management scheme provided satisfactory anaesthetic level while preserving the capacity of central cardiovascular regulation. SAP was recorded through a pressure transducer (Gould P23XL, Valley View, OH, U.S.A.) and a universal amplifier (Gould 20‐4615‐58).…”
Section: Methodsmentioning
confidence: 88%
“…The increase in ICP was used as our experimental index for penile erection (Chen et al ., 1992a, 1992b; 1997; Chang et al ., 1998a, 1998b; 2000; 2001). In brief, a 26‐gauge needle filled with saline and connected to a pressure transducer (Gould 23ID) was inserted into the corpus cavernosum on one side.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation